IMPLEMENTASI KEBIJAKAN PENGELOLAAN KARCIS OBJEK WISATA PEMANDIAN AIR PANAS BORA DI DINAS PARIWISATA KABUPATEN SIGI - Dahlia, Dahlia; Daswat, Daswat; Darwis, Darwis (Katalogis, 2020)
The study aims at finding out and analyzing the implementation of policies on ticketing management in Bora Hot Spring, the tourism object of Sigi Regency. The main theory as the reference of this study is the Implementation of Policy by Edward III who looks at policy implementation focusing on Â 4 aspects, those are; (1) the aspect of communication, (2) the aspect of resources, (3) the aspect of dispositionÂ and (4) the aspects of bureaucratic structure. The research method uses a qualitative descriptive approach. The location of this study is located in Bora Hot Springs, the tourism object of Sigi Regency involving 7 selected purposevely informers. Data collection is conducted using Interactive model by Miles and Huberman. Based on the results of the study, the implementation of ticket management policies on the Bora Hot Springs Tourism object is still not optimal. It could be seen from the 4 aspects in measuring the policy implementation by Edward III, there one aspect that wa still inadequate, namely the aspect of human resources, where it was inadequate in terms of quality aspect, it was seen from the existence of personal interests by some people that did not impose to ticket payment, regarding to facilities and infrastructure resources in which need to be improved, as well as the budgetary resources that still need to be incrased so that ticket management for Bora Hot Springs can be managed optimally.